Therapeutic options in the treatment of benign prostatic hyperplasia - Sandhu, Jaspreet S (Dove Medical Press, 2009)
Current theraputic options for the treatment of symptomatic benign prostatic hyperplasia (BPH) are reviewed. Therapeutic options for mild lower urinary tract symptoms (LUTS), as defined by the American Urological Association, are generally treated medically. Moderate to severe LUTS can be treated medically or with surgical therapy. Current medical and surgical treatments for LUTS secondary to BPH are reviewed and evolving treatments are explored.